Cooperation During the Designation and Management of the Dogger Bank - Kooij, van der, Marieke (Utrecht Journal of International and European Law, 2011)
The Dogger Bank is a potential transboundary marine protected area (MPA) located in Dutch, German, Danish and UK waters. International and EU legal instruments contain provisions requiring cooperation during the designation and pro- tection/management of the Dogger Bank as an MPA. Many of the cooperation requirements are not specified; therefore, Member States are left with a certain discretion as to the extent and form of the implementation of the required cooperation. Since this cooperation began taking place, the required standards seem to be being met. However, the exact meaning of the requirement for cooperation included in the Marine Strategy Framework Directive (MSFD) is questionable; it remains to be seen whether the current cooperation complies with this Directive. In order to optimise the current cooperation practice, an increasing role for the European Commission (EC) and the Habitats Committee within the process of the designation and management of the Dogger Bank as an MPA could be strived for. Furthermore, when looking at the relevant legal instru- ments an amendment of Oslo-Paris (OSPAR) Recommendation 2003/3 provides an option to further establish a specific legal basis for cooperation.